2021
DOI: 10.2196/26643
|View full text |Cite
|
Sign up to set email alerts
|

Personalization of Conversational Agent-Patient Interaction Styles for Chronic Disease Management: Two Consecutive Cross-sectional Questionnaire Studies

Abstract: Background Conversational agents (CAs) for chronic disease management are receiving increasing attention in academia and the industry. However, long-term adherence to CAs is still a challenge and needs to be explored. Personalization of CAs has the potential to improve long-term adherence and, with it, user satisfaction, task efficiency, perceived benefits, and intended behavior change. Research on personalized CAs has already addressed different aspects, such as personalized recommendations and an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Moreover, detailed information may be more effective as patients can reread a message at any time in the history record of the chat window [48]. In-depth responses also convey an informative, interpretive, and deliberative communication style, whereas shorter messages suggest a paternalistic style [54]. Some scholars have found that patients expect to receive detailed explanations and a large amount of information from their physicians in the internet hospital [55].…”
Section: Impact Of Physicians' Communication Style On Patient Satisfa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, detailed information may be more effective as patients can reread a message at any time in the history record of the chat window [48]. In-depth responses also convey an informative, interpretive, and deliberative communication style, whereas shorter messages suggest a paternalistic style [54]. Some scholars have found that patients expect to receive detailed explanations and a large amount of information from their physicians in the internet hospital [55].…”
Section: Impact Of Physicians' Communication Style On Patient Satisfa...mentioning
confidence: 99%
“…First, paying patients are already confident in their physicians' competence, and more detailed information (as a credibility signal) is therefore unlikely to enhance patients' service satisfaction. Second, patients with a serious illness typically seek immediate and helpful guidance [54]. Based on the above discussion, we hypothesize the following:…”
Section: Moderating Effect Of Free Servicementioning
confidence: 99%
“…Using sample dialogues also aided in refining the flow of the conversation to help make it more personal and engaging to the participant. Personalizing elements of chatbot conversations promote engagement in chatbots used in health education and commercially [38,39]. NLP is not yet feasible for those without access to specialized technical resources.…”
Section: Conversation Tracks and Personalizationmentioning
confidence: 99%
“…worked on the extraction of health goals and topic boundary detection as research towards building a coach that can have SMS conversations. Beinema, op den Akker et al (2021) investigated the adjustment of coaching strategies to users' motivation to live healthy in a CA application, andGross et al (2021) investigated personalisation of interaction styles (e.g., deliberative or paternalistic) for CAs in chronic disease management. Furthermore, even though this is a one-way manner of communication mostly aimed at an utterance level, the process of tailoring messages that are sent to the user has been researched in relationship with users' stage of change, stage of change and personality and gender, activity and self-efficacy…”
mentioning
confidence: 99%